COMPARATIVE ANALYSIS OF NEOGEODYNAMICS OF THE BALTIC SYNECLISE AND THE NORTHERN SLOPE OF THE VORONEZH ANTECLISE A - A. O. Agibalov; V. A. Zaitsev; A. A. Sentsov (Геодинамика и тектонофизика)
The paper presents the results of comparative neogeodynamic analysis of the Baltic syneclise and northern Voronezh anteclise based on structural-geomorphological interpretation, digital elevation model (DEM) processing procedure using LESSA program [Zlatopolsky, 2011], seismic analysis, and computer geodynamic modeling. Both regions are seismically active areas of the East European Platform. The automated DEM analysis showed that they are dominated by NW-striking lineaments oriented across the strike of the neoextension axis. Computational neogeodynamic models imply that the areas under consideration develop in shear environment, with the compression axis oriented northwest. Another important result of modeling is numerical correlation between earthquake energy, interpolated over the Baltic syneclise, and the probability of occurrence of ruptures: the Pearson correlation coefficient is 0.58 for the sedimentary cover and 0.42 for the basement. For the northern Voronezh anteclise, a correlation was found between the epicentral density of earthquakes and "Fracture regions" parameter, with reference to which there were distinguished the areas with the probable occurrence of new short-extension ruptures (the Pearson correlation coefficient is 0.41). This parameter is informative for contouring seismically active parts since the areas with probable occurrence of new ruptures, occupying 39 % of the northern Voronezh anteclise, account for 71 % of earthquake epicenters. Structuralgeomorphological interpretation yielded a high degree of correlation between relief and active faults identified as "weak" zones to which the earthquake epicenters are largely confined. Therefore, both regions considered are characterized by high sedimentary-cover seismic activity, develop in shear stress field, with the stress axis oriented northwest, and have similar orientations of linear elements of relief and "weak" zones.The analysis of the earthquake recurrence curves shows considerable differences between seismic regimes of the northern Voronezh anteclise and the Baltic syneclise, and those between the sedimentary-cover and basement seismicity of the latter. These differences may be due the fact that the stressed state of the Voronezh anteclise is affected by active structures of the Urals and Caucasus, and that the upwarping Fennoscandian shield is largely responsible for neodeformations of the Baltic syneclise. Practical significance of the study is concerned with the identification of earthquake source zones.